INFLUENCE OF RELIGIOUS MODERATION IN THE CURRICULUM: AN ANALYSIS OF THE TRANSFORMATION OF THE ASWAJA CURRICULUM IN CONTEMPORARY ISLAMIC EDUCATION - Amin, Muhamad; Febriarsita Eka Sasmita; Imam Bukhari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study analyzes the transformation of the Aswaja curriculum in fostering a moderate and character-driven generation through a document-based review of the LP Ma’arif NU curriculum guidelines. A qualitative approach is employed using document analysis and NVivo-style thematic coding to identify patterns, themes, and embedded values within the curriculum. The findings reveal a shift from a normative-doctrinal approach toward an integrative-transformative model that internalizes values of religious moderation such as tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) across learning outcomes, pedagogical strategies, and both intra- and extracurricular activities. The curriculum functions not only as a means of knowledge transmission but also as a medium for developing critical awareness and student character through dialogical, reflective, and contextual approaches. These findings highlight that integrating local values rooted in religious traditions significantly contributes to inclusive, tolerant, and anti-radicalism-responsive education, while strengthening curriculum design, teacher capacity, and sustainable educational ecosystems.